2010
DOI: 10.2135/cropsci2010.02.0109
|View full text |Cite
|
Sign up to set email alerts
|

Variation among Half‐Sib Families and Heritability for Biomass Yield and Other Traits in Lowland Switchgrass (Panicum virgatum L.)

Abstract: Switchgrass (Panicum virgatum L.) is a main herbaceous species projected for use as feedstock in biofuel production. Understanding the nature of genetic variation for biomass yield and other important traits in switchgrass would aid cultivar development. The aim of this study was to estimate the genetic component of variation and narrow‐sense heritability for biomass yield and several morphological and phenological traits in lowland switchgrass. Thirty‐seven half‐sib families were evaluated during 2007–2009 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 33 publications
13
76
4
Order By: Relevance
“…According to the BIC, there was a very strong evidence against the reduced models in which the family effects are assumed to be zero. This result confirmed a significant amount of genetic variation among full-sib families for the traits studied, indicating a significant contribution of additive genes in the expression of these traits (Bhandari et al, 2010). This result is also in accordance with other studies in which the family effect was significant used in this study.…”
Section: Resultssupporting
confidence: 92%
“…According to the BIC, there was a very strong evidence against the reduced models in which the family effects are assumed to be zero. This result confirmed a significant amount of genetic variation among full-sib families for the traits studied, indicating a significant contribution of additive genes in the expression of these traits (Bhandari et al, 2010). This result is also in accordance with other studies in which the family effect was significant used in this study.…”
Section: Resultssupporting
confidence: 92%
“…In upland tetraploid switchgrass, among-and-within-family selection proved moderate heritability (0.41) for plant height, with greater values for selection of increased height, while heritability for tiller count was generally low (0.06), and flowering date was estimated to have high heritability (0.75) overall in both selection direction (Price et al 2014). In lowland switchgrass, according to the research of Bhandari et al (2010), half-sib families were different for biomass yields and other traits, suggesting that the presence of additive gene effect in controlling these traits. Heritabilities were moderate (0.40-0.70) for heading, flowering, and plant spread.…”
Section: Breeding Switchgrass For Bioenergy Productionmentioning
confidence: 99%
“…Talbert et al (1983) reported high narrow-sense heritabilities (0.91 or above) for switchgrass maturity based on a lowland population of 33 half-sib families. Using 37 lowland half-sib families of one lowland population, Bhandari et al (2010) reported moderate to high (0.58-0.74) narrow sense heritabilities for heading and flowering time. Bhandari et al (2011) observed heritability estimates for heading date were larger based on full-sib families than on half-sib families, suggesting dominant gene effect or epistasis likely played an important role.…”
mentioning
confidence: 97%
“…These heritability estimates are similar to those made for biomass yield (0.29-0.65) and related traits (plant height <0.27, tillering 0.28-0.48, etc.) in other populations of switchgrass [38][39][40].…”
Section: Localization Of Qtl Flanking Markers In the Switchgrass Genomentioning
confidence: 99%